Required coefficient of friction analyses in running - Vidal, A. B.; Monezi, L. A.; Sarro, K. J.; Mazoni, A. F.; Pinto, H. T.; Barros, R. M. L. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to analyze the possible alterations in the required coefficient of friction (RCOF) in running under the following conditions: a) barefoot against shod; b) self-selected velocity and cadence versus imposed cadence and c) along three running phases (initial contact, mid-stance and propulsion). Two Kistler force plates were used to measure the horizontal and vertical components of ground reaction forces in order to calculate the RCOF. Statistical differences were found for cadence and phase factors. Barefoot-Shod conditions did not present statistical differences. An interaction between velocity and phase of cycle was found. At propulsion phase, an increased RCOF were revealed, especially with the interaction of an imposed cadence. In conclusion, the present study supports the relevance of RCOF as a variable affecting and being affected during running to be taken into consideration at many experimental conditions.